Proteus mirabilis: A rare cause of pneumonia, radiologically mimicking malignancy of the lung - Saif ullah; Ramin Saadaat; Hidayatullah Hamidi; Ahmed Maseh Haidary (Clinical Case Reports, 2023)
Key clinical message Lesions that are suspected for malignancy need be managed by a multidisciplinary team. Utilization of radiological as well as pathological diagnostic modalities ensures correct diagnosis and thus timely intervention. Abstract Introduction Proteus mirabilis is a Gram‐negative rod. It is a highly motile bacterium that belongs to the Enterobacteriaceae. Lung infection and pneumonia caused by p. mirabilis is extremely rare and occurs in patients with chronic debilitation or chronic lung disease. Case Presentation A 65‐year‐Old Woman presented with dry cough, dyspnoea on exertion, and chest pain of 4 months' duration. She received multiple medications including antibiotics but without any resolution of her symptoms. Computed Tomography scan of the chest was performed reported a tumor in the upper lobe of the left lung with multiple associated pulmonary nodules. The impression was that of metastatic lung disease with superimposed acute infection. Accordingly, the patient was reevaluated and a diagnostic bronchoscopy with multiple endobronchial biopsies and broncho‐alveolar lavage was done. The gram stain showed Gram‐Negative Bacilli and the bacteria identified P. mirabilis. Conclusion Mass lesions suspected for malignancy should be managed with involvement of multiple medical disciplines, to ensure correct and timely diagnosis. This is to avoid miss‐management.